Selective Esterification Of Glycerol With Lauric Acid To Monolaurin Using 12-Tungstophosphoric Acid Incorporated Sba-15 - Yong, Hoo Peng (2016)
The synthesis of highly effective superacid incorporated heterogeneous catalysts for selective monoglyceride production via esterification of glycerol with long chain fatty acid was attempted in this study. Aiming to exploit the superacidity from 12-tungstophosphoric acid (HPW), it was supported onto SBA-15 via post impregnation and direct synthesis methods. The catalysts’ surficial, structural and chemical properties were revealed and elucidated using various characterization techniques. Post impregnated catalysts showed the highly uniformed mesopores (55 – 59 Å) with high surface areas (323 – 600 m2/g) retained from the parent SBA-15. Strong acidity was exerted by the Keggin-structured HPW anions that were successfully deposited within the mesopores. High catalytic performances were detected, with high lauric acid conversions (72 – 78 %) and monolaurin yields (46 – 54 %). On the other hand, directly synthesized catalysts were identified to be silica materials with high surface areas (169 – 521 m2/g) with uniformed mesopores (45 – 60 Å). Distinct differences in terms of material characteristic and catalytic performances could be identified. Less dispersion of HPW among directly synthesized catalysts was detected when compared to those of post impregnated ones. Formation of tungsten oxides was also found for 30wt% and 40wt%-HPW/DS, ultimately causing lowered acidities found among the directly synthesized catalysts. Relatively lower lauric acid conversion (71 – 75 %) and monolaurin yield (47 – 52 %) were also detected for the directly synthesized catalysts. Nevertheless, the synthesized catalysts showed promising potential as much shorter reaction time (from 20 to 3 hours) was needed compared to those reported. With 40wt%-HPW/IM selected as the most potential catalyst, simple power law and mechanism based kinetic study was performed. Results revealed that the catalyzed reaction might follow a reaction pathway via a combination of nucleophilic substitution and LangmuirHinshelwood mechanism. Unfortunately, poor reusability of 40wt%-HPW/IM (up to one time only) was observed. Such poor reusability was evidently due to the heavy leaching of the HPW anions from the supports. As such, further improvement of the catalyst by impregnation of HPW onto calcium modified SBA-15 was performed. With a two-step impregnation method, insoluble calcium HPW acid salt within the mesopores of the parent SBA-15 was formed. Similar to the post impregnated catalysts earlier, HPW impregnated CaSBA-15 catalysts consisted of highly uniformed mesopores (58 – 63 Å) with high surface areas (564 – 604 m2/g). Strong acidities (0.680 – 0.714 mmol NH3 equivalent per gram), sourced from the retained Keggin HPW was found for all of the modified catalysts. The novel silica – calcium – HPW bridged between SBA-15 and HPW was found to not only able to maintain high catalytic performances, but also showed superior reusability with no apparent loss of catalytic performance after 3 cycles.